A single soul in two bodies: The multiple configuration of otherness in Martín Adán’s La casa de cartón (The Cardboard House) - García Flores, Diego (2022)
This article proposes a review of the different possibilities that help to recognize the strategies that represent a conceptual link with the theme of alterity or otherness in Martín Adán’s La casa de cartón. As a starting point, the idea of the splitting of the narrator in the figure of the character Ramón, who could function as a projection or masking of the authorial figure, through the reading of his diaries and, above all, of the «poemas underwood».